Utilización de la metodologia de la gestion de procesos para la distribuidora discardenas (distribuidor de bebidas de consumo moderado) - Arevalo., Carlos (2011)
This paper presents the results obtained by applying the Methodology of Process Management to Distribuidora DISCARDENAS (sales of moderate drinking). For applying this methodology, it has been taken into account the perception of customers of DISCARDENAS regarding the sales service it offers, through a market research that includes a series of steps that will help us determine which processes are failing, in order to run the system application to be implemented to improve the processes of that company. During the development of this project it is shown the use of univariate and bivariate statistical techniques (contingency tables), which help identify deficiencies in processes and propose possible solutions to them, through Methodology Systems (Balanced Scorecard), and Strategic Management Control Systems.